2020
DOI: 10.1525/collabra.17213
|View full text |Cite
|
Sign up to set email alerts
|

Moving Developmental Research Online: Comparing In-Lab and Web-Based Studies of Model-Based Reinforcement Learning

Abstract: For years, adult psychological research has benefitted from web-based data collection. There is growing interest in harnessing this approach to facilitate data collection from children and adolescents to address foundational questions about cognitive development. To date, however, few studies have directly tested whether findings from in-lab developmental psychology tasks can be replicated online, particularly in the domain of value-based learning and decision-making. To address this question, we set up a pipe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 28 publications
8
50
1
Order By: Relevance
“…However, further work is needed to explore this. Nonetheless, to our knowledge, our study is the first to replicate this effect in an online study, although we note that Nussenbaum and colleagues also showed an age-effect of decision-making balance in children, adolescents, and young adults in an online version of the two-stage task (Nussenbaum et al, 2020). This suggests that the effect of age is quite robust and can be replicated both in-lab and online.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…However, further work is needed to explore this. Nonetheless, to our knowledge, our study is the first to replicate this effect in an online study, although we note that Nussenbaum and colleagues also showed an age-effect of decision-making balance in children, adolescents, and young adults in an online version of the two-stage task (Nussenbaum et al, 2020). This suggests that the effect of age is quite robust and can be replicated both in-lab and online.…”
Section: Discussionsupporting
confidence: 63%
“…While the original two-stage Markov tasks were conducted in-person ( Gläscher et al, 2010 ; Daw et al, 2011 ), a handful of studies using the task have been conducted online ( Gillan et al, 2015 ; Nussenbaum et al, 2020 ). In general, web-based studies benefit from convenience (i.e., eliminating travel) and larger samples ( Berinsky et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…How similar are the findings from in-person and online experiments? Positive results come from an online study about reinforcement learning (Nussenbaum et al, 2020), which replicated a main effect of age from the original in-person study (Decker et al, 2016). In other developmental research, online data replicated a mediating role for abstract-reasoning ability in the link between age and model-based learning (Chierchia et al, 2019).…”
mentioning
confidence: 82%
“…Thus, it is important to ensure that -despite these potential sources of variability -data collected remotely with young children participants is comparable to data obtained from in-person assessments. While recent work has shown that remote data collection procedures can replicate the effects of lab-based studies in older children and adolescents (Nussenbaum et al, 2020), it remains an open question whether data collected remotely with young children is comparable to data obtained in-person.…”
Section: Increasing Need For Remote Data Collection With Children Participantsmentioning
confidence: 99%